Gus Nadir as an Ideal Role Model: Sociological Study on Counter Narratives Towards Caliphate Issue in Twitter - Mubarokah, Lailatin; Tanggang, Nadya Utari Br (UIN Sunan Kalijaga Yogyakarta, 2019)
Due to internet contribution in supplying informations, radicalism has inevitably followed the stream and been disseminated in every layers of society. As one of the most used platform, social media becomes the biggest contributor in sharing ideology. Pesantren as religious institution that ought to spread values of peace religion has also been affected. The debate in internet is getting more crowded nowadays, especially, the debate about caliphate whichcreated pro and cons group. This paper picks Twitter since it ranks as the highest turnover information platform, including in caliphate debate, to discuss how does the debate run, what are the user talking about in terms of it, what are the anvils they use. Out of this crowd, comes Gus Nadir as the representative figure of campus and pesantren in giving counter narrative for the caliphate narratives in Twitter, also as the antithesis of pesantren as radicalism producer. By using sociological approach which based on social media this paper offers Gus Nadir as the ideal role model in giving counter narrative towards radicalism, especially caliphate notion, who is capable in knowledge, reliable in giving statements, and casual in explaining, for all people, especially pesantren people.